(untitled) (MMIT Proceedings, 2024)
It is not always possible to find the solution of the system of linear algebraic equations by exact methods. Therefore, numerical methods are used to solve such equations. This work shows the method of finding the solution of the system of linear algebraic equations using the simple iteration method, which is an approximate method of finding the solution. Also, the solutions of the program for the equation worked out in this way are compared.